KOMUNIKASI INSTRUKSIONAL GURU DALAM KEGIATAN EKSTRAKURIKULER PROGRAM DA’I DI SD ISLAM TERPADU Az-ZUHRA ISLAMIC SCHOOL DI PEKANBARU - Puji Azani; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The da’i program at SD IT Az-Zuhra Islamic School is a program whose goal is to develop the character and lecturing abilities of the students. Fostering and training elementary school students is not an easy matter, because they are very young and had never lectured in public before. The new students learned lecturing after they joined the da’i group until they get sufficient expertise in public speaking. The purpose of this study is to determine the methods, media, and communication obstacles that occur in the training process at the Az-Zuhra Islamic School. This study used qualitative research methods. The research was conducted at the SD IT Az-Zuhra Islamic School Pekanbaru. Informant selection is done by purposive technique. Data collection techniques consist of observation, interviews, and documentation. Data analysis technique use descriptive analysis according to Miles and Huberman. This study used the Extension of participation, Triangulation and Adequacy of references for the validity checking technique of the data.            The results showed that the instructional communication of the teacher in teaching children the da’i program was very adequate to foster and train students. It can be seen from the teacher’s expertise in lecturing and also from the ability of the teacher in teaching students so that the teacher gets the trust of the students. The teacher also applies visual and audio-visual media to facilitate the teaching and learning process. There are various methods used by the teacher in teaching and improving students abilities, including the lecture method, the command method, the training method, and the question and answer method. Then there are several types of obstacles. Obstacle in the communicator is the differences in memory and comprehension of each student. Obstacle to the channel is the absence of projector and speakers in the teaching and learning process, and obstacle to the communicant is they are not focus and causing the learning atmosphere to be disturbed. Keywords: Instructional Communication, Da’i Program, Islamic School